2012
DOI: 10.1126/science.1228250
|View full text |Cite
|
Sign up to set email alerts
|

Fishing for Answers off Fukushima

Abstract: The triple disaster of the March 11, 2011, earthquake, tsunami, and subsequent radiation releases at Fukushima Dai-ichi were, and continue to be, unprecedented events for the ocean and for society. More than 80% of the radioactivity from Fukushima was either blown offshore or directly discharged in to the ocean from waters used to cool the nuclear power plants (1). Although offshore waters are safe with respect to international standards for radionuclides in the ocean (2), the nuclear power plants continue to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 7 publications
2
81
1
Order By: Relevance
“…In general, demersal fish, which live and feed in close proximity to bottom sediments, have higher Cs activities than pelagic fish, and specimens of both types caught off of Fukushima Prefecture have levels higher than those in prefectures located north or south of the FDNPPs (Buesseler 2012) (Figure 5). Some of the highest Cs activities found in fish in coastal waters (25,800 Bq kg −1 ww) were measured in two greenlings caught close to the Ota River in August 2012 that were thought to have migrated from the FDNNP harbor .…”
Section: Figurementioning
confidence: 99%
“…In general, demersal fish, which live and feed in close proximity to bottom sediments, have higher Cs activities than pelagic fish, and specimens of both types caught off of Fukushima Prefecture have levels higher than those in prefectures located north or south of the FDNPPs (Buesseler 2012) (Figure 5). Some of the highest Cs activities found in fish in coastal waters (25,800 Bq kg −1 ww) were measured in two greenlings caught close to the Ota River in August 2012 that were thought to have migrated from the FDNNP harbor .…”
Section: Figurementioning
confidence: 99%
“…A number of marine organisms ingested radionuclides into their body via the water and their diet. As a result, high concentrations of radiocesium were detected in almost all fi sh that inhabit the coast of Fukushima Prefecture within a year after the tsunami (Buesseler 2012 ). The level of contamination has decreased over time, and has now stabilized at a low level in pelagic fi sh species and invertebrates (Wada et al 2013 ;Sohtome et al 2014 ).…”
Section: Introductionmentioning
confidence: 91%
“…The results revealed that radiocesium contamination was transferred quickly to freshwater and marine ecosystems, and elevated radiocesium concentrations were detected in many fi sh and invertebrates (Fisheries Agency 2012 ). These concentrations decreased over time in most of the epipelagic fi sh and neustonic organisms (Buesseler 2012 ). However, some demersal fi sh off the coast of Fukushima and some freshwater fi sh in central and northern Honshu Island continue to exhibit higher radiocesium concentrations (Tateda et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%